2016
DOI: 10.20342/ijsmm.2.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Potential Coir Fibre Composite for Small Wind Turbine Blade Application

Abstract: Abstract-Natural fibers have been developed as reinforcement of composite to shift synthetic fibers. One of potential natural fibers developed is coir fiber. This paper aims to describe potential coir fiber as reinforcement of composite for small wind turbine blade application. The research shows that mechanical properties ( tensile, impact, shear, flexural and compression strengths) of coir fiber composite have really similar to wood properties for small wind turbine blade material, but inferior to glass fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…journal.ump.edu.my/ijame ◄ few decades, the use of natural fibers like ramie [14], hemp [15], jute [16], sisal [17], kenaf [18], banana [19], gnetum [20], coir [21] fibers and others has been developed as a composite reinforcement in lieu of synthetic fibers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…journal.ump.edu.my/ijame ◄ few decades, the use of natural fibers like ramie [14], hemp [15], jute [16], sisal [17], kenaf [18], banana [19], gnetum [20], coir [21] fibers and others has been developed as a composite reinforcement in lieu of synthetic fibers.…”
mentioning
confidence: 99%
“…These fibers have a continuous fiber structure and strength natural woven and can reduce weight from 10% to 30% (which is the main thing in automotive design). Bakri et al [21], reported that coir reinforced polymer composites are potential using as an alternative material for making windmill blades. Natural fibers have different properties and characteristics from synthetic fibers, thus requiring different machining parameters.…”
mentioning
confidence: 99%
“…The life cycle analysis for bamboo has also been investigated to determine its characteristics with that of glass fiber blades. The group concluded that using bamboo was the best option for wind turbine blades [37]. Mechanical characteristics of coir fiber composites have also been investigated [38].…”
Section: Natural Fibermentioning
confidence: 99%
“…Due to many current environmental problems, researchers are constantly focusing on replacing the existing material system of wind turbine blades with natural biodegradable materials. 90 Natural fibers such as flax, 91 coir 92 and bamboo 93 are easily available and low processing cost. 94 Natural fiber-reinforced composites have some advantages those cannot be obtained by synthetic fiber-reinforced composites which include low density, low cost, non-abrasive properties and biodegradability.…”
Section: New Environmentally Friendly Blade Materialsmentioning
confidence: 99%